Utility of Transcutaneous Capnography for Optimization of Non-Invasive Ventilation Pressures - Prashant N Chhajed; Simone Gehrer; Kamlesh V Pandey; Preyas J Vaidya; Joerg D. Leuppi; Michael Tamm; Werner Strobel (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Nocturnal Non-invasive Positive Pressure Ventilation (NPPV) is the treatment of choice in patients with chronic hypercapnic respiratory failure due to hypoventilation. Continuous oxygen saturation measured with a pulse oximeter provides a surrogate measure of arterial oxygen saturation but does not completely reflect ventilation. Currently, Partial Pressure of Arterial (PaCO2) measured by arterial blood analysis is used for estimating the adequacy of ventilatory support and serves as the gold standard Aim: To examine the safety, feasibility and utility of cutaneous capnography to re-titrate the non-invasive positive pressure ventilation settings in patients with chronic hypercapnic respiratory failure due to hypoventilation. Materials and Methods: Twelve patients with chronic hypercapnic respiratory failure prospectively underwent complete polysomnography and cutaneous capnography measurement on the ear lobe. Non-invasive ventilation pressures were adjusted with the aim of normalizing cutaneous carbon dioxide or at least reducing it by 10 to 15 mmHg. Sensor drift for cutaneous carbon dioxide of 0.7 mmHg per hour was integrated in the analysis. Results: Mean baseline cutaneous carbon dioxide was 45.4 + 6.5 mmHg and drift corrected awake value was 45.1 + 8.3 mmHg. The correlation of baseline cutaneous carbon dioxide and the corrected awake cutaneous carbon dioxide with arterial blood gas values were 0.91 and 0.85 respectively. Inspiratory positive airway pressures were changed in nine patients (75%) and expiratory positive airway pressures in eight patients (66%). Epworth sleepiness score before and after the study showed no change in five patients, improvement in six patients and deterioration in one patient. Conclusion: Cutaneous capnography is feasible and permits the optimization of non-invasive ventilation pressure settings in patients with chronic hypercapnic respiratory failure due to hypoventilation. Continuous cutaneous capnography might serve as an important additional tool to complement diurnal arterial carbon dioxide tension values.